Utilization of coconut (Cocos nucifera, Linn.) sapal in the laboratory scale production of barbeque spice flavored rice - Pineda, Mylene Joan N.; Tavora-Mateo, Liwayway (1993.)
A formulation for the laboratory scale production of kroepeck using a combination of coconut sapal and rice flour was developed. The best ratio of coconut sapal to rice flour was found to be 15:85, as evaluated by a panel of 10 members based on appearance, shape, color, and texture of the samples. Using the same combination but with varying levels of barbecue spice flavor, panelists also evaluated the color, texture and flavor of the kroepeck samples. The most acceptable amount of flavoring added was 10 percent of the flour mixture. Proximate analysis of the final product showed that it contains 7 percent protein. 30 percent carbohydrates. 26.1 percent fat, 34.3 percent fiber, 2.3 percent ash, and 0.3 percent moisture. A consumer survey was also conducted in three different areas to determine the acceptability of the final product. The product was rated by the majority as "like very much." Furthermore, cost analysis of the product showed that a pack of 50 grams only costs P1.50 which was less than what the consumers indicated that they were willing to pay for.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coconut products